EFFECT OF LEBOSOL® FOLIAR FERTILIZERS ON ENERGY AND PROTEIN TRANSFORMATION ALONG THE ECO-TECHNICAL CHAIN ‘SEED MATERIAL – GRAIN YIELD OF MAIZE’ - L. Ivanov; K. Uzunova; D. Penkov (Trakia Journal of Sciences)
The aim of the study was to calculate the “multiplication effect” between the included gross energy (crude protein) with the seeds and the same, obtained with the grain yields in the eco-technical system “seed material – soil – grain yield”, so as the influence of some foliar fertilizers Lebozol® on it. For variants were investigated – control without foliar fertilizers and three experimental – trated with Aminosol + Lebosol Zin, Nutriplant 36 and Mix for maize respectively. The multiplication effects were: - For the Gross energy: Control – 1048.7 times (with variations from 833.36 to 1287.73); First experimental – 1099 times (with variations from 876.49 to 1343.75) – 4.55% exceeding the control; Second experimental – 1093.3 times (with variations from 863.57 to 1341.62) – 4.08% exceeding the control; Third experimental – 1078.8 times (with variations from 862.5 to 1322.54) – 2.80% exceeding the control. - For the crude protein: - Control – 997.2 times (with variations from 803.28 to 1224.43); First experimental - 1050 times (with variations from 837.58 to 1284.1) – 11.86% exceeding the control; Second experimental – 1131.3 times (with variations from 893.7 to 1338.42) - 11.86% exceeding the control; Third experimental - 1047.7 times (with variations from 837.71 to 1284.57) – 4.83% exceeding the control.